Pola Komunikasi Forum Kerukunan Umat Beragama dalam Menjaga Toleransi pada Masyarakat Kecamatan Jembrana Bali - Nuriya, Ummi; BR, Rosyadi (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
The people of Jembrana sub-district who have different religions have let the government to create a forum that respects one another and tolerates the differences that occur. The importance of maintaining patterns of communication and interaction between people to be able to maintain friendly relations with each other. The exsitence of FKUB in jembrana sub-district is very important considering its diverse religious population to prevent conflict and uphold tolerance. The focus of this research is: 1) What is the communication pattern of the religious harmony forum in maintaining tolerance in the jembrana sub-district community jembrana regency Bali? 2) How is the community’s response to the forum for religious harmony in jembrana sub-district jembrana district Bali?. This study uses qualitative research with a case study type. Data collection techniques using observation, interviews, and documentation. The data analysis technique uses techniques from Miles and Huberman. The conclusions from the research results are: 1) The communication patterns applied by FKUB in maintaining the value of tolerance in the jembrana sub-district community are by building interpersonal communication, group communication, and mass communication. Communication is carried out face to face (interpersonal) then each religious leader speaks verbally to his ummah to convey his own message, and group communication can be coordinated with religious leaders who are administrators of the FKUB jembrana district with cross-faith and the mass media. 2) the response of the jembrana sub-district community to the existence of the jembrana district FKUB was very enthusiastic and good.